Assessment of environmental impacts by mining activities: A case study from Jhansi open cast mining site - Uttar Pradesh, India - Amit Pal*, Rajeev K Niranjan; Manjesh Kumar, Gayatri Singh, (Journal of Experimental Sciences, 2010)
Mining and its allied activities have taken big strikes during the last century contributing significant infrastructure development and raising the living standards of mankind. However, they have also brought in their wake, degeneration and degradation of natural resources, pollution, health risk and socio-ecological instabilities. Bundelkhand region, occupying almost 71818km2 in the central planes of India, is known for its rich deposits of pyrophyllite, moram, salt peter, granite, diasporas, sand, etc. Currently, there are around 325 active mining sites in Jhansi district alone. Deforestation, dust generation, water, air and noise pollution and resource depletion are common hazards associated with opencast mining widely prevalent in this region. The present paper attempts to reveal the base line environmental quality and socio-economic setting in and around such mining sites with special reference to the effects on the air, water, changes of land use pattern and occupational health effects of mine workers etc. It also attempts to provide a framework for management strategies to improve the environmental conditions in the mining sites and its adjoining environments.